Design, synthesis and properties of triple-color hyperbranched polymers derived from poly(9, 9-dioctylfluorene) with phosphorescent core tris(1-phenylisoquinoline)iridium(Ⅲ). (February 2016) - Sun, Jing; Wang, Hua; Yang, Tao; Zhang, Xinwen; Li, Jie; Zhang, Tiaomei; Wu, Yuling; Chen, Weihua; Wong, Wai-Yeung; Xu, Bingshe
Abstract: A series of triple-color hyperbranched polymers based on poly(9, 9-dioctylfluorene) (PF) were designed and synthesized, in which phosphorescent tris(1-phenylisoquinoline)iridium(Ш) (Ir(piq)3 ) acts as red core and poly[(9, 9-dioctylfluorene-2, 7-diyl)-alt-(benzo[2, 1, 3]thiadiazol-4, 7-diyl)] (PFBT) is inserted as green-emission segment. The synthesized polymers have good thermostability, film forming ability and high fluorescence quantum yield. By tuning the contents of red core and green-emission segment, the optimized triple-color hyperbranched polymer is acquired, named PF-BT250-Ir(piq)3 25. Furthermore, the PF-BT250-Ir(piq)3 25 is utilized as single emission layer in white polymer light emitting diode with the configuration of ITO/PEDOT:PSS (50 nm)/PF-BT250-Ir(piq)3 25 (80 nm)/TPBI (40 nm)/LiF (1 nm)/Al (100 nm). The diode exhibits a maximum luminous efficiency of 1.60 cd/A, a maximum luminance of 3267 cd/m 2 and the Commission Internationale de l'Eclairage coordinate of (0.32, 0.34) very close to the pure white point of (0.33, 0.33). Graphical abstract: Triple-color hyperbranched polymers based on poly(9, 9-dioctylfluorene) (PF) with phosphorescent tris(1-phenylisoquinoline)iridium(Ш) (Ir(piq)3 ) as red core and poly[(9, 9-dioctylfluorene-2, 7-diyl)-alt-(benzo [2, 1, 3]thiadiazol-4, 7-diyl)] (PFBT) as green segments were designed and synthesized. Highlights: Triple-color hyperbranched white-light polymers were designed and synthesized. Phosphorescent Ir(piq)3 acts as red core inserted to fluorescent main chains. The synthesized polymers have good thermostability and film forming ability. The diodes exhibit excellent electroluminescent performance.